FIRM-SPECIFIC CHARACTERISTICS, MARKET RISKS AND ASSET QUALITY OF DEPOSIT MONEY BANKS IN NIGERIA - Toluwa Celestine Oladele; Peters Ade Sanni (Malete Journal of Accounting and Finance)
The decline in asset quality stimulates the interest to investigate the effect of firm-specific characteristics and asset quality of Deposit Money Banks (DMBs) in Nigeria. Hence, this study examined the asset quality of these banks from firm-specific characteristics and market risks dimension. Secondary data was adopted for this study and the data for the firm-specific characteristics was extracted from the audited financial statements of the sixteen selected quoted DMBs in Nigeria as at December 2018. The data for the market risk variables was extracted from the Central Bank of Nigeria website and the World Development Index. Static panel regression was employed as the estimation technique. Results showed that diversification, capital adequacy, profitability and leverage are the bank-specific factors that determine asset quality. Inflation and financial crisis are the market risks variables that have a significant effect on DMBs’ asset quality. Based on these findings, the study concluded that diversification, profitability, capital adequacy, leverage, inflation and financial crisis are the major drivers of bank’s asset quality in Nigeria. In line with the findings, the study recommended that banks should strive to maintain the prudential threshold for capital adequacy as this will help them absorb shocks and withstand losses that may arise in the reasonable cause of doing business. Also, the regulatory authorities (CBN) should strive to reduce the high inflationary trend in the country